Turkish tourism and hospitality students’ international posture: attitudes toward the international community - Hulisi Binbasioglu; Suleyman Nihat Sad (Tourism and Hospitality Management, 2019)
Purpose– The purpose of this paper is to define Turkish tourism students’ stands regarding international community, i.e. international posture, which is a neglected area of research in terms of tourism and foreign language education curricula. Design – This study was designed based on a baseline survey model followed by an associational design. The former phase aimed to determine the tertiary Turkish tourism students’ stands regarding the international community. The second phase explored the relevance of participants’ international posture to gender, school type, and employment background in jobs requiring contact with foreigners, perceived proficiency in languages including English, German, and Russian. Methodology – Data were first analyzed using descriptive statistics, then compared by gender and school type using t-test and ANOVA, and finally correlations between students’ stands regarding the international community and employment background and perceived proficiency in different languages were tested. Findings – Results suggested that Turkish tourism students see themselves moderately connected to the international community and are moderately interested in international affairs and are moderately ready to interact with people other than Turkish. Originality of the research – The productivity and sustainability of tourism industry depend largely on the well-educated staff; however, the quality of education of tourism students, especially on intercultural awareness, is an under-researched issue.